Impact of Brand Equity on Brand Loyalty through Social Media Marketing Activities - Dr. Yasir Tanveer; Zainab Imtiaz; Dr. Anum Tariq (Indus Journal of Social Sciences, 2025)
With the rise of brand equity in competitive markets, understanding its role in creating brand loyalty has become essential. Grounded in branding and consumer behaviour theories, this study examines how brand equity influences brand loyalty, with self-recognition as a mediator and social media marketing activities as a moderator. The research explores how consumers’ perceptions of brand equity enhance self-recognition, which, in turn, strengthens their loyalty to the brand. Furthermore, social media marketing plays a critical role in improving consumer engagement, potentially moderating the relationship between brand equity and loyalty. Using a quantitative research approach, data were collected from consumers in Faisalabad who actively engage with brands on social media. SPSS (Statistical Package for the Social Sciences) was used to analyze relationships among variables, applying descriptive statistics, reliability analyses, correlation analyses, and regression techniques to examine the proposed model. The findings of this study offer valuable insights for marketers and brand managers, enabling them to develop effective strategies that enhance brand loyalty through brand equity management, self-recognition alignment, and social media engagement. This research contributes to the literature on brand management and digital marketing by highlighting the psychological and social mechanisms that connect brand equity with consumer loyalty.